MANAJEMEN PEMASARAN PENDIDIKAN BERBASIS STRATEGI PENENTUAN PASAR SASARAN (Lembaga Pengembangan Kinerja Dosen, 2022)
This research is to know the concept of education marketing management based on target market determination strategy. This research is a qualitative type through literature study. Literature study is another term for literature review, literature review, theoretical study, theoretical basis, literature review, and theoretical review. When determining market segments, it is necessary to pay attention to key market segment variables, such as demographic, psychographic, geographic and benefit segmentation. These four segmentations divide the consumer market in order from the general and massive to the most specific, namely a) demographic segmentation, namely: segments that make market groups based on age, education, gender, family size and income identification; b) geographic segmentation, namely identifying based on area, climate, population density or market physical conditions; c) psychographic segmentation, namely the segment that identifies consumers based on people's lifestyles and consumer personalities by observing a person's activities, tastes, opinions or interests; and d) benefit segmentation, which is a segment that focuses on the expected use of a product or service that is offered and provided.